Unexpected CD4 cell count decline in patients receiving didanosine and tenofovir-based regimens despite undetectable viral load - Negredo, Eugenia; Moltó, José; Burger, David; Viciana, Pompeyo; Ribera, Esteve; Paredes, Roger; Juan, Manel; Ruiz, Lidia; Puig, Jordi; Pruvost, Alain; Grassi, Jacques; Masmitjà, Elisabeth; et al. (AIDS (London), 2004)
We recently observed a significant CD4 cell count decline in patients receiving didanosine (ddI) 400 mg, tenofovir (TDF) and nevirapine (NVP), despite virological suppression. We identified from our computerized patient database subjects who initiated combinations containing ddI and/or TDF for reasons other than virological failure, including simplification or intolerance. Changes in total, CD4+ and CD8+ lymphocyte counts since the initiation of therapy were analysed retrospectively. Plasma concentration of ddI was prospectively determined in eight of these patients receiving ddI 400 mg + TDF + NVP and 3 weeks after a ddI dosage reduction. A total of 302 patients were studied. A significant decrease in CD4 and CD8 and in total lymphocyte counts was only seen in subjects receiving ddI standard dose + TDF-containing regimens, despite the maintenance of viral suppression. More than 50% of these patients showed a decline of more than 100 CD4 cells at 48 weeks. In contrast, subjects not receiving ddI + TDF together experienced the expected progressive increase in CD4 T-cell counts. Plasma levels of ddI were elevated in all patients receiving the standard ddI dose + TDF. DdI plasma levels significantly decreased when patients weighting > 60 kg reduced ddI dose to 250 mg, achieving similar levels to those generated by ddI 400 mg without TDF. Co-administration of ddI at standard doses plus TDF appears to exert a deleterious effect on CD4 and CD8 counts. Although lymphocyte toxicity related to excessive ddI plasma levels could explain our findings, other mechanisms cannot be excluded. Pharmacokinetic data suggest ddI dose reduction when coadministered with TDF.